2008
DOI: 10.1016/j.mce.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids affect the reproductive functions in teleosts and amphibians

Abstract: Following the discovery in the brain of the bonyfish Fugu rubripes of two genes encoding for type 1 cannabinoid receptors (CB1A and CB1B), investigations on the phylogeny of these receptors have indicated that the cannabinergic system is highly conserved. Among the multiple functions modulated by cannabinoids/endocannabinoids through the CB1 receptors one of the more investigated is the mammalian reproduction. Therefore, since studies performed in animal models other than mammals might provide further insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The presence of cb1 in frog brain, mainly in the forebrain and midbrain—as also observed from fish to mammals [14, 41, 60, 61]—has suggested that eCS is able to control reproductive functions through a central regulation. This is in line with the discovery that hypothalamic immortalized GnRH secreting neurons possess a complete eCS, CB1 included [62] and that AEA inhibits GnRH release from rat mediobasal hypothalamus [63].…”
Section: Relationship Between Ecs and Gnrh Systemmentioning
confidence: 88%
See 1 more Smart Citation
“…The presence of cb1 in frog brain, mainly in the forebrain and midbrain—as also observed from fish to mammals [14, 41, 60, 61]—has suggested that eCS is able to control reproductive functions through a central regulation. This is in line with the discovery that hypothalamic immortalized GnRH secreting neurons possess a complete eCS, CB1 included [62] and that AEA inhibits GnRH release from rat mediobasal hypothalamus [63].…”
Section: Relationship Between Ecs and Gnrh Systemmentioning
confidence: 88%
“…During the course of the years, the eCS has been characterized and studied from a functional point of view in many species [1417]. In this regard, the use of nonmammalian animal models has contributed to a better comprehension about the eCS actions, especially in several reproductive events [16, 1820].…”
Section: Introductionmentioning
confidence: 99%
“…The basal crosstalk between ECS and GnRH is evolutionarily conserved, since it has been described also in lower vertebrates (Chianese et al, , 2011bCottone et al, 2008. In both amphibians and teleost fish, CB1 was detected in the forebrain, the encephalic macro-area containing the anterior preoptic area, the encephalic region mainly involved in GnRH activity and in the control of gonadotropin discharge (Cottone et al, 2003Lam et al, 2006;Migliarini et al, 2006;Meccariello et al, 2008;Valenti et al, 2005).…”
Section: Ppar Response Elements P P a Rmentioning
confidence: 92%
“…In males, ECS modulates the progression of spermatogenesis, spermatozoa functions and the activity of testicular somatic cells in mammalian, non-mammalian vertebrates as well as in invertebrates. (Battista et al, 2012;Cacciola et al 2008;Cobellis et al, 2006;Cottone et al, 2008;Grimaldi et al, 2009;Maccarrone et al, 2003Maccarrone et al, , 2005Pierantoni et al, 2009, Schuel et al, 1991Wang et al, 2006). In females, ECBs represent fertility signals in folliculogenesis, follicle maturation, oocyte maturation and ovulation (El-Talatini et al, 2009).…”
Section: Are Ecbs and Kisspeptin Putative Local Modulators Of Gnrh/gomentioning
confidence: 99%
“…In zebrafish, on the other hand, only one CB1 gene has been detected (Lam et al 2006), while two CB2 genes (CB2A and CB2B) are present (Rodriguez-Martin et al 2007). In goldfish, a CB1 sequence has been cloned (Valenti et al 2005; Cottone et al 2005) and the distribution of the receptor has been analyzed in the retina (Yazulla et al 2000), CNS (Valenti et al 2005; Cottone et al 2005) and gonads (Cottone et al 2008). On the other hand, CB2 had not yet been identified in goldfish.…”
Section: Introductionmentioning
confidence: 99%